Economic Discourse on Population Policy Dynamics and Sustainable Development in Libya - Omar Al-Mahdi (Budapest International Research and Critics University, 2011)
This paper examines the dynamics of population policy and its implications for sustainable economic development in Libya from an economic perspective. Libya’s demographic structure, characterized by a relatively young population and fluctuating growth patterns influenced by political instability, presents both opportunities and challenges for national development. The study explores how population policies influence key economic indicators such as labor supply, human capital development, public expenditure, and long-term economic productivity. Drawing on economic policy analysis, secondary data, and development frameworks, the paper analyzes the role of government institutions, economic planners, international organizations, and policy stakeholders in shaping population policy discourse in Libya. It highlights how economic considerations such as employment generation, resource allocation, and fiscal sustainability intersect with population dynamics in determining development outcomes. The paper argues that while policymakers often recognize the economic implications of population growth, the effectiveness of population policy in Libya is constrained by institutional weaknesses, limited data systems, and socio-political uncertainties. Furthermore, differing perceptions among stakeholders regarding population growth whether as a driver of economic strength or a burden on limited resources continue to shape policy debates. The findings suggest that successful population policy in Libya requires a balanced approach that integrates demographic objectives with economic planning, emphasizing investment in education, workforce development, and inclusive growth strategies. The paper concludes that strengthening policy coordination, improving data-driven decision-making, and aligning population strategies with economic development goals are essential for achieving sustainable development in Libya.